SIMP Canosa: Integrated System for Monitoring and Prevention of environmental crime Video surveillance and satellite imagery for the territory monitoring - Zotti, Massimo (GEOmedia, 2015)
A Decision Support System improving the capacity of the Municipality forces to prevent and fight crimes such as traffic of dangerous waste, illegal landfills, illegal buildings or archaeological and natural heritage damages.